UNSUR EKOLOGI DALAM PERIBAHASA BANJAR ( ECOLOGY ELEMENTS IN BANJARESE PROVERBS) - Norvia Norvia (Universitas Lambung Mangkurat, 2021)
Abstract Ecology Elements in the Banjarese Proverbs. This research is motivated by the researcher's interest in preserving the Banjarese proverbs which is now starting to fade in its meaning due to ignorance of the ecological forms of flora, fauna, and culture which are used as a kias word in Banjarese proverbs. This study aims to describe (1) the ecological form of flora in the Banjarese proverbs (2) the ecological form of fauna in the Banjarese proverbs (3) The form of cultural ecology in the Banjarese proverbs. Sources of data are obtained from books and informants. The book used as a data source is a collection of Banjarese proverbs by Aliansyah Jumbawuya. The results of this study found that of the three classifications there were even more specific classifications, namely, (1) the Banjarese proverbs ecological flora consisting of vegetables, fruits, and wild plants, (2) Banjarese proverbs ecology fauna consisting of fauna habitat in land and water, and (3) the Banjarese proverbs of cultural ecology consists of three categories, namely home architecture, tools and living equipment, and systems of thought. Key words: ecology, oral tradition, Banjarese proverb Abstrak Unsur Ekologi Sastra dalam Paribasa Banjar. Penelitian ini dilatarbelakangi oleh ketertarikan peneliti untuk melestarikan peribahasa Banjar yang sekarang mulai kabur dalam pemaknaannya akibat ketidaktahuan akan wujud ekologi flora, fauna, dan budaya yang dijadikan kata kias dalam peribahasa Banjar. Penelitian ini bertujuan mendeskripsikan (1) Wujud ekologi flora dalam peribahasa Banjar (2) Wujud ekologi fauna dalam peribahasa Banjar (3) Wujud ekologi budaya dalam peribahasa Banjar. Sumber data didapat dari buku dan informan. Adapun buku yang dijadikan sumber data adalah kumpulan peribahasa Banjar karya Aliansyah Jumbawuya. Hasil penelitian ini menemukan dari tiga klasifikasi tersebut di dapat penggolongan yang lebih spesifik lagi yakni, (1) peribahasa Banjar ekologi flora terdiri dari sayur-sayuran, buah-buahan, dan tanaman liar, (2) peribahasa Banjar ekologi fauna terdiri dari fauna habitat di darat dan di air, dan (3) peribahasa Banjar ekologi budaya terdiri dari tiga kategori yakni arsitektur rumah, peralatan dan perlengkapan hidup, dan sistem berpikir. Kata-kata kunci: unsur ekologi, tradisi lisan, paribasa Banjar